The cost of sanctions: Estimating lost trade with gravity - Julian Hinz (Kiel Institute for the World Economy (IfW), 2017)
Economic sanctions are a frequently used tool of foreign policy. Constraining trade flows towards or from the target country is supposed to coerce its government into changing certain policies. However, sanctions constitute an obstacle to trade, thereby affecting flows of all countries, including those of sanctioning countries themselves. I gauge the global impact of three recent sanctions regimes using a structural gravity framework and quantify the "lost trade" in a general equilibrium counterfactual exercise. Each of the episodes, sanctions against Iran, Russia and Myanmar, are instructive in their own way, due to the different nature of bilateral trade and severity of measures applied.
Keywords: F51; F14; F13; F52; 330; sanctions; embargo; General equilibrium counterfactuals; foreign policy